Tobacco Cultivation Regimentation: An Ethnographic Treatise from Pagergunung Village, Bulu, Temanggung - Pangeran Putra Perkasa Alam Nasution; Heddy Shri Ahimsa-Putra; Bambang Hudayana (Universitas Andalas, 2023)
Indonesia, as the sixth largest tobacco-producing country in the world, has participated in the Framework Convention on Tobacco Control (FCTC) by issuing compromise regulations through Government Regulation (PP) No. 109 of 2012. This regulation regulates restrictions on tobacco production and distribution of products made from tobacco raw materials. Furthermore, PP No. 109 of 2012 determines the increases in tobacco excise rates and the determination of limits on nicotine levels also sparked unrest among tobacco farmers in the Temanggung area. This article attempts to explain the insistence of farmers, especially in the eastern slope of Mount Sumbing, Pagergunung Village, Bulu District, Temanggung, in maintaining tobacco cultivation even though they are faced with an anti-tobacco campaign from the FCTC. The continued cultivation of tobacco can be understood as a form of regimen of cultivated plants. This article is an anthropological study with a regimentation theoretical perspective and ethnographic approach as a research method which presents the research results. From this research, it is known that the cultivation regimen is controlled by mythology, tobacco trade tricks, and the pretext of tradition as a socio-cultural surplus.